(untitled) (Iraqi Journal of Medical Sciences, 2025)
Background: Corticosteroid and antiviral agents are widely used to treat the acute phase of Bell’s palsy but their effectiveness is still uncertain. Objective:This study aimed to compare the theraputic effect of Acyclovir and steroid versus steroid alone, in combanation with physiotherapy, in patients with Bell’s palsy. Methods:This interventional study was conducted in Al-Yarmok Teaching Hospital and Al-Kadhimiya Teaching Hospital, during the period from July 2007 to July 2008. It involved (58) patients, who were divided into two groups: Group A; 28 patients, treated by steroid for 10 days. Group B; 30 patients, treated by steroid and acyclovir for 10 days. Physiotherapy for one month for both groups was followed and reassessment according to House-Brackmann grading system was done after completion of each therapy. Results:The recovery of patients treated with steroid and Acyclovir was (66.6%), while the patients treated with steroid alone was (46.4%), however, the diffrence was statistically insignificant. After one month physiotherapy the responses were (76.7% and 53.5%) for patients in both groups respectively. Conclusion:The addition of Acyclovir therapy in Bell’s palsy has not found to be benefitial. Keywords:Bell’s palsy, Corticosteroid, Antiviral agents, Physiotherapy.